Chinese anti-dumping measures against Republic of Korea - BUTH, Dadiya (KDI School, 2018)
Many countries around the world began using anti-dumping measures once again after 2011 and in recent years, it was well-known that People’s Republic of China (Henceforth China) was notorious for this kind of measures and at the same time, this country also emerges as Republic of Korea’s (Henceforth Korea) important trading partner. Due to the significance of trade between these two large economies, it is crucial to study the relationship between anti-dumping measures and trade flow between these two countries. Consequently, this study uses Poisson pseudo-maximum-likelihood (PPML) to investigate the impact of Chinese anti-dumping measures on import quantity and import value from Korea. The empirical finding in this paper indicates that Chinese anti-dumping measures have adverse effect on trade flow from Korea. Statistically, Chinese import quantity and import value from Korea decline by 18% and 13% respectively while Chinese anti-dumping measures are in place.
Thesis(Master) --KDI School:Master of Public Policy,2018